Hydrolysis of cellulosic bamboo biomass into reducing sugars via a combined alkaline solution and ionic liquid pretreament steps. (April 2017) - Kassaye, Samuel; Pant, Kamal K.; Jain, Sapna
Abstract: Dilute acid hydrolysis of cellulosic biomass is not only controlled by the reaction conditions such as temperature, concentration of acidic catalyst and hydrolysis time but also by changing the physical aspects of the reaction media. Therefore, overcoming the insolubility of cellulose by the use of effective solvent without having to derivatize their basic functional groups is of tremendous advantage in the utilization of lignocellulosic biomass. Ionic liquids are considered as the most suitable solvents to dissolve cellulosic biomass and overcome the recalcitrant nature of lignocellulosic biomass. This study investigates the valorisation of bamboo biomass regenerated from alkaline solution and ionic liquid pretreament steps followed by dilute sulphuric acid hydrolysis. Lignin removal from the biomass as a result of pretreatment steps was analysed by crystallinity index determination, surface morphology and thermal stability analysis. The solid biomass materials were characterized using FTIR, XDR, SEM, TGA and Elemental analysis techniques to investigate the effect of the pretreatment steps on the properties of the original bamboo biomass. Alkaline treatment was found to be effective against lignin and hemicellulose removal. However, it did not remove the complexity of the cellulosic portion of the biomass with equal success. The crystallinity of the recovered cellulosic biomass could be effectively reduced by using the ionic liquid pretreatment. Investigation revealed that the yield of total reducing sugars increased to 64% after alkaline solution pre-treatment in comparison to only 30% yield of reducing sugar in the untreated biomass sample. After both pretreatment steps, the yield of reducing sugar further increased to 80%. Highlights: Alkaline solution and ionic liquid pretreatment studied for fractionation of bamboo biomass. The effect of pretreatment steps on crystallinity index of cellulosic biomass assessed. The pretreatment steps improved the yield of TRS from 30 to 80%.